Extensão Rural em terras indígenas no estado de São Paulo: agrofloresta e turismo em aldeias Guarani - Santos, Tatiane Ribeiro dos (2019)
Regarding ethnodevelopment initiatives with traditional communities, indigenous peoples occupy a recognized space within public policies. In the context of family farming, in which indigenous people are beneficiaries by law, a set of rural extension actions is developed in the State of São Paulo based on the State Program for Sustainable Rural Development (PDRS): Microbasins II, Market Access, which contemplates the "Strategy of Participation of Indigenous Populations." In this context, the objective of the research was to evaluate the conceptions, ways of implementation, the perceptions and social, cultural and environmental impacts of the activities of this program in Aldeia Boa Vista and Aldeia Itaoca Tupi, where agroforestry and rural tourism systems were implemented, respectively.The methodological orientations involved bibliographic and documentary survey and case study.It was noted that the changes of government directly affect the actions of public rural extension mainly impacting family farming. Indigenous peoples are even more disadvantaged because they do not have However, agroecology as well as the education and formation of socio-technical networks have proved to be positive instruments to overcome the challenges related to interculturalism faced by extensionists in the field. Bureaucratic obstacles were the biggest difficulties for the implementation of the Program. However, the final assessment is positive: there have been advances in ATER services provided to indigenous communities in the state of São Paulo and the initiatives have created references that can guide the creation and / or improvement of policies aimed at strengthening and emancipating indigenous people in the environment rural.